Special Issue: Christian Philosophical Perspectives on Sustainable Development - Massink, Henk (Philosophia reformata, 2018)
In this introductory article, the authors first briefly present the debate on the meaning of sustainability and consider the question of how to connect the concept of sustainability with a Christian—in particular, Reformational—way of doing philosophy. After examining the various uses of Dooyeweerdian philosophy in this regard, this introduction closes with an overview of the contributions to this special issue.